Application of Pressurized Cooking and Freezing Technique to Improve the Quality of Instant Ledok - Wrasiati, Luh Putu; Wijaya, I Made Anom Sutrisna; Suter, I Ketut (Agriculture and Natural Resources, 2014)
Ledok is atraditional non-rice, forage-like food from Nusa Penida Island, Klungkung regency, Bali Province, Indonesia. The main ingredients of Ledok are corn and cassava tubers, which are frequently mixed with red beans, peanuts and vegetables. To be accepted as a commercial food product, in-depth research into the formulation, process engineering, quality control, shelf life and marketing are required. In this research, optimization of the preliminary cooking process using a pressurized cooking treatment (pressure cooker) with a variation of 6–12 min cooking time followed by freezing at -20 oC for 24–72 hr was carried out to improve the quality of instant Ledok. The objectives of this research were to study the effect of pressurized cooking and the freezing time on the quality of instant Ledok and to determine the appropriate pressurized cooking and freezing time of instant Ledok. The analysis performed in this research included analysis of yield, water absorption, cooking time and proximate analysis. The results indicated that the longer the pressurized cooking and freezing time, the smaller the yield, the greater the absorption of water and the shorter the cooking time. The results of proximate analysis indicated that the variation in pressurized cooking and freezing time did not affect the levels of protein, fat, crude fiber, ash and carbohydrate content of instant Ledok. The most appropriate cooking and freezing times that resulted in the best quality characteristics of instant Ledok were 12 min pressurized cooking time and 72 hr freezing time.